Fisheries management for different angler types - John Curtis; Benjamin Breen (The Economic and Social Research Institute (ESRI), 2016)
On-site survey data from coarse and game angling sites in Ireland is used to estimate count data models of recreational angling demand. To investigate the existence of preference heterogeneity across angler-types, three demand functions are estimated according to angler type; coarse, game and a combination of both. Comparison of these demand functions indicates that the fishery characteristics which drive demand differ depending on angler-specific characteristics. For example treating all anglers as an homogeneous group led to results suggesting angling demand is higher where there is a greater provision of angling services (such as guide-hire and tackle shops). While this relationship pertained for the game angling demand function, angling service levels had no effect on coarse angling demand. Water quality, which was not found to be significant in driving demand in the combined case, was identified as a significant determinant of angling demand in game fisheries. Overall the results strongly support the need to specifically address angler characteristics when analysing angler preferences. Improved survey design that attains more detailed information such as anglers' quarry-type, skill level, etc. will improve the ability of analysts to understand angler preferences and provide more effective policy recommendations.
Keywords: 330; angling; travel cost; game angling; coarse angling